A REVIEW PAPER ON HOME AUTOMATION SYSTEM USING GOOGLE ASSISTANT - Ms. Preeti U. Melikatti; Mr. Vinayak V. Palmur (International Journal of Innovations in Engineering Research and Technology, 2021)
The paper presented here deals with the Home Automation scenario in the world today, It reviewed many aspects of home automation technologies like web based technologies, App based technologies, Remote technologies etc. The review is helpful for the researchers and will be instrumental for further work and advancements to be carried out in the said field of Home Automation.